AID overexpression leads to aggressive murine CLL and nonimmunoglobulin mutations that mirror human neoplasms - Morande, Pablo Elias; Yan, Xiao-Jie; Sepulveda Yañez, Julieta Haydee; Seija, Noe; Marquez, Maria Elena; Sotelo, Natalia; Abreu, Cecilia; Crispo, Martina; Fernandez-Grana, Gabriel; Rego, Natalia; Bois, Therence; Methot, Stephen P.; et al. (My University, 2021)
Most cancers become more dangerous by the outgrowth of malignant subclones with additional DNA mutations that favor proliferation or survival. Using chronic lymphocytic leukemia (CLL), a disease that exemplifies this process and is a model for neoplasms in general, we created transgenic mice overexpressing the enzyme activation-induced deaminase (AID), which has a normal function of inducing DNA mutations in B lymphocytes. AID not only allows normal B lymphocytes to develop more effective immunoglobulin-mediated immunity, but is also able to mutate nonimmunoglobulin genes, predisposing to cancer. In CLL, AID expression correlates with poor prognosis, suggesting a role for this enzyme in disease progression. Nevertheless, direct experimental evidence identifying the specific genes that are mutated by AID and indicating that those genes are associated with disease progression is not available. To address this point, we overexpressed Aicda in a murine model of CLL (E mu-TCL1). Analyses of TCL1/AID mice demonstrate a role for AID in disease kinetics, CLL cell proliferation, and the development of cancer-related target mutations with canonical AID signatures in nonimmunoglobulin genes. Notably, our mouse models can accumulate mutations in the same genes that are mutated in human cancers. Moreover, some of these mutations occur at homologous positions, leading to identical or chemically similar amino acid substitutions as in human CLL and lymphoma. Together, these findings support a direct link between aberrant AID activity and CLL driver mutations that are then selected for their oncogenic effects, whereby AID promotes aggressiveness in CLL and other B-cell neoplasms.
Keywords: Activation-induced (cytidine) deaminase